Low-Dose Anti-HIV Drug Efavirenz Mitigates Retinal Vascular Lesions in a Mouse Model of Alzheimer’s Disease - El-Darzi, Nicole; Mast, Natalia; Buchner, David A.; Saadane, Aicha; Dailey, Brian; Trichonas, Georgios; Pikuleva, Irina A. (Frontiers in Pharmacology, 2022)
A small dose of the anti-HIV drug efavirenz (EFV) was previously discovered to activate CYP46A1, a cholesterol-eliminating enzyme in the brain, and mitigate some of the manifestation of Alzheimer’s disease in 5XFAD mice. Herein, we investigated the retina of these animals, which were found to have genetically determined retinal vascular lesions associated with deposits within the retinal pigment epithelium and subretinal space. We established that EFV treatment activated CYP46A1 in the retina, enhanced retinal cholesterol turnover, and diminished the lesion frequency >5-fold. In addition, the treatment mitigated fluorescein leakage from the aberrant blood vessels, deposit size, activation of retinal macrophages/microglia, and focal accumulations of amyloid beta plaques, unesterified cholesterol, and Oil Red O-positive lipids. Studies of retinal transcriptomics and proteomics identified biological processes enriched with differentially expressed genes and proteins. We discuss the mechanisms of the beneficial EFV effects on the retinal phenotype of 5XFAD mice. As EFV is an FDA-approved drug, and we already tested the safety of small-dose EFV in patients with Alzheimer’s disease, our data support further clinical investigation of this drug in subjects with retinal vascular lesions or neovascular age-related macular degeneration.